REGIONAL IDENTIFICATION AND SELF-IDENTIFICATION OF THE RESIDENTS OF THE YENISEI SIBERIA REGION: THE LINGUOCULTURAL ASPECT - Shmulskaya , Larisa; Slavkina , Inga; Vekkesser , Maria; Mamayeva , Svetlana (Revista Inclusiones, 2020)
The relevance of the problem under investigation is caused by the growing process of globalization, which, except the positive results, includes the risks of leveling out the ethnic and territorial uniqueness. The identification of the verbal means of forming and representing the regional selfidentification can contribute to the development of an effective image strategy of the region. The present paper aims to describe the verbal markers of regional identification and self-identification of the inhabitants of the Yenisei Siberia region in the linguistic and cultural aspect. The work uses the cultural approach to the analysis of the facts of the language. Contextual and intent analysis methods, as well as surveys allowed the authors of the paper to identify lexical and grammatical units essential for solving the problem of attributing an individual to a certain territorial community.